Prospective Teachers’ Learning and Practicing Assessment in Teaching Practicum: Comparative Perspective in Pre-Service Teacher Education Programmes - Ghulam Behlol, Malik; Fox, Alison; Massud, Faiza; Arshad, Sahiba (Journal of Development Policy Research and Practice (JoDPRP), 2024)
This study examines the challenges associated with implementing learning-supportive assessment during teaching practicum, while also exploring the roles of University Tutors (UT), Cooperative Teachers (CT), Prospective Teachers (PT), and Heads of Practicum Schools (HPS) in selected universities in Pakistan and the United Kingdom (UK). Using the qualitative case study approach, data was collected through lesson observations of UT in pre-service teacher education settings and PT in practicum schools. Additionally, interviews were conducted with UT and HPS, and a Focus Group Discussion (FGD) was held with PT. The study concludes that, in comparison to their UK counterparts, PT in Pakistan encounter significant barriers to implementing learning-supportive assessment in practicum school settings. These barriers include large class sizes, a lack of institutionalised collaboration between universities and schools, inadequate lesson modelling, ineffective feedback practices, assignments that emphasise lower-order thinking skills, and limited opportunities to utilise technology in school settings. Based on the findings, the study recommends the implementation of a new assessment policy that expands examinations beyond mere knowledge recall to include competency assessment. This policy should incorporate adherence to Pakistani teacher standards and the use of reflective portfolios. Moreover, it is advised to provide training for UT and CT in enacting assessment techniques rather than solely providing theoretical knowledge. Additionally, the study proposes the development of problem-solving assignments or projects that require PT to engage in reflection, critical thinking, imagination, and multidimensional contributions. JEL Classification Code: I20